The Role of Democratic Parenting Style in Shaping Learning Independence in Fifth Grade Students of SDN 001 Samarinda - Anshari, Muhammad Akmal; Imawati, Diana; Mariskha, Silvia Eka (Jurnal Psikologi Terapan, 2024)
This study aims to investigate the impact of democratic parenting on the learning independence of fifth-grade students at SDN 001 Samarinda. The learning independence of students is significantly influenced by their environment, particularly by the parenting style, which can positively affect the development of independent learning attitudes in children. This research uses a quantitative method with simple regression analysis to examine the relationship between democratic parenting and students' learning independence. Data were collected through the learning independence scale and the Parental Authority Questionnaire Revised (PAQ-R) scale, which was adapted into Indonesian. The results show that democratic parenting has a positive effect on learning independence, with students who experience high levels of democratic parenting demonstrating better learning independence. Conversely, low levels of democratic parenting are associated with lower learning independence. This study concludes that democratic parenting can enhance students' learning independence and highlights the importance of parents adopting a democratic parenting style to support the development of their children's learning independence.